Analysis of the Chemical Composition, Antimicrobial, and Antioxidant Qualities of Microwave and Supercritical CO2-Extracted Lavender Essential Oils Cultivated in a Hyperarid Region of Türkiye - Gedikoglu, Ayca; Ozturk, Hale Inci; Ozcoban, Afranur (MDPI, 2024)
This study compares the chemical composition, antioxidant capacity, and antibacterial properties of lavender essential oils extracted using microwave-assisted extraction (MAE) and supercritical CO2 extraction (SCDE). Gas chromatography-mass spectrometry analysis revealed that the MAE oil contained higher levels of linalyl acetate (36.19%) and linalool (28.29%) compared with the SCDE oil, which had values of 28.72% and 27.48%, respectively. The MAE oil also showed superior antioxidant activity, with DPPH IC50 values of 72.99 mg/mL and FRAP values of 1.31 mM Fe2+/g, compared with 80.84 mg/mL and 1.14 mM Fe2+/g for the SCDE oil. Antibacterial tests indicated that the MAE oil exhibited lower MIC values, demonstrating twice the antibacterial activity against Bacillus cereus NRRL B3711, Bacillus subtilis PY79, and Enterococcus faecalis ATCC 29212 compared with the SCDE oil. These results highlight the superior bioactivity of MAE-extracted lavender oil, making MAE a preferred method for high-quality oil extraction from drought-affected lavender plants.
Keywords: GC-MS; bioactivity; microbial inhibition; extraction techniques; volatile components; LAVANDULA-ANGUSTIFOLIA; AROMATIC PLANTS; EXTRACTION; Biochemistry & Molecular Biology; Chemistry